Município de Araputanga - antes e depois - Colosso, Cristiane Otília; Lima , Eliene Xavier de; Bento , Miriam Furtado; Schiavinato , Ricardo Leandro; Santos , Rosimar Evangelista dos (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf